Visibility and differentiation: systemic testing in a developing country context. Issue 2 (2nd April 2016) - Hoadley, Ursula; Muller, Johan
ABSTRACT: Why has large‐scale standardised testing attracted such a bad press? Why has pedagogic benefit to be derived from test results been downplayed? The paper investigates this question by first surveying the pros and cons of testing in the literature, and goes on to examine educators' responses to standardised, large‐scale tests in a sample of low socio‐economic status (SES) schools in the Western Cape, South Africa. The paper shows that teachers and school managers have an ambivalent attitude to tests, wary of the reputational costs they can incur, but also curious about the differentiated picture test results can give them as they learn to 'read' the underlying codes embedded in the results. The paper concludes that a focus on what tests make visible and a recognition of the pedagogic agency of teachers points to potential pedagogic benefits of systemic tests.